Influence of price, health aspect, taste, and smell on making decision of Myanmar’s peanut oil purchasing - S. Hafianti; E. F. Perez; T. Win; A. N. M. Ansori; H. T. Sam (Пищевые системы, 2025)
This study aims to investigate the factors that influence consumer purchasing decisions regarding peanut oil brands in Myanmar, specifically examining the impact of price, health benefits, and taste and smell on purchasing behavior. A quantitative research approach was employed to analyze the data collected from 255 participants who are social network friends’ netizens living in Yangon region. The gathered data was analyzed by using the logistic regression statistical tool. Tests such as Likelihood Ratio test, Wald test, the Hosmer-Lemeshow test, Cox and Snell R-square, Nagelkerke R-square and Omnibus test were used in this study for the model fitting purpose to achieve its objectives. The results show that peanut oil price had a significant impact on consumer purchasing decisions, while health considerations also played a role in decision-making. However, taste and smell did not significantly contribute to the prediction of the relationship between the dependent and independent variables.